2011
DOI: 10.1177/0018720811417254
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Factors Affecting Trust in Human-Robot Interaction

Abstract: The findings provide quantitative estimates of human, robot, and environmental factors influencing HRI trust. Specifically, the current summary provides effect size estimates that are useful in establishing design and training guidelines with reference to robot-related factors of HRI trust. Furthermore, results indicate that improper trust calibration may be mitigated by the manipulation of robot design. However, many future research needs are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
788
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,311 publications
(883 citation statements)
references
References 44 publications
(39 reference statements)
37
788
1
Order By: Relevance
“…Freedy et al [8] investigated the effects of mixed initiative robot control on a user's trust within a military tele-robotics setting. Hancock et al [11] carried out a meta-analysis of empirical results from the HRI trust literature, and established quantitative estimates of various factors influencing trust across different interaction domains. Yagoda [21] gathered trust assessments from a broad audience by showing videos of human-robot interactions and eliciting users' trust responses through an online crowd-sourcing framework.…”
Section: Related Workmentioning
confidence: 99%
“…Freedy et al [8] investigated the effects of mixed initiative robot control on a user's trust within a military tele-robotics setting. Hancock et al [11] carried out a meta-analysis of empirical results from the HRI trust literature, and established quantitative estimates of various factors influencing trust across different interaction domains. Yagoda [21] gathered trust assessments from a broad audience by showing videos of human-robot interactions and eliciting users' trust responses through an online crowd-sourcing framework.…”
Section: Related Workmentioning
confidence: 99%
“…The fitness function itself is then constructed by summing intensity functions for motivating sensor data as follows: A synthetic fitness landscape generated with Eq. 16.13 using 9 motivating points at positions (4, 4), (4,18), (4,19), (4,22), (12,4), (12,12), (20,4), (20,12) and (21,22) …”
Section: Motivated Particle Swarm Optimization For Adaptive Task Allomentioning
confidence: 99%
“…Unless these internal differences are transparent to a human collaborator, there may be a perception that there is less consistency of action between individuals. Existing work has found that such performance based factors play a key role in trust development between humans and robots [12,44].…”
Section: Implications For Reliabilitymentioning
confidence: 99%
“…Human-robot interaction (HRI) research typically explores interactions in which the robot plays a supportive or collaborative role for the human user [4]. However, there are circumstances in which robots may fail to meet these requirements, either through errors in processing the interaction scenario, or failure to adapt to changing HRI scenario circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are circumstances in which robots may fail to meet these requirements, either through errors in processing the interaction scenario, or failure to adapt to changing HRI scenario circumstances. Furthermore, reliability and error rates of robots have both been identified as important factors in user trust towards robots [4]. Recent work has explored the social impact of a robot's fault or error, in terms of user cooperation [9], and whether an apology from a robot can mitigate the negative impact of the mistake [10].…”
Section: Introductionmentioning
confidence: 99%